The Best Measurement of Tax Aggressiveness in Predicting Corporate Risk - Verani Carolina; Oktavianti Oktavianti (Universitas Muhammadiyah Surakarta, 2021)
This study aims to see which measurement of tax aggressiveness is the best in predicting corporate risk. There are various kinds of tax aggressiveness measurements that have been used by many researchers, including Effective Tax Rate (ETR), Cash Effective Tax Rate (CETR), Book Tax Different (BTD), Permanent Book Tax Different (PBTD), Discretionary Permanent Different (DTAX), and Abnormal Book Tax Different (ABTD). This study used a sample of manufacturing companies listed on the Indonesia Stock Exchange. The data processing method used is Confirmatory Factor Analysis to see which measurement is the best in predicting corporate risk. The results showed that tax aggressiveness can predict corporate risk, and DTAX is the best measurement in predicting corporate risk. DTAX is the best measurement because of it’s ability to capture conforming tax avoidance doing by companies (unlike other measurements that only capture non-conforming tax avoidance).Keywords: tax aggressiveness, conforming tax avoidance, non-conforming tax avoidance, and corporate risk.